PENINGKATAN KEMAMPUAN LITERASI DIGITAL MENGGUNAKAN TEKNOLOGI QUIZIZZ DALAM PENERAPAN BEST PRACTICE DI SATUAN PENDIDIKAN PPM AL IKHLAS - Andi Rosman N; Musdar M; Ummu Kalsum (Jurnal Abdi Insani, 2023)
Professional teachers are teachers who have pedagogical, personality, professional and social competencies. One of the pedagogical abilities that teachers must have is being able to utilize technology for learning implementation. In today's digital era, teachers must be able to become technology literate teachers, in order to create a more interesting and interactive learning atmosphere. This must also be owned by teachers in the Al Ikhlas PPM education unit which will then become partners. Based on the purpose of implementing this activity is to increase partner knowledge in using technology in learning. In addition, it will also improve partner skills in using Quizizz as an interactive learning media. The method used is through training, mentoring and mentoring which is integrated in workshop activities. This method was chosen to provide opportunities for teachers to participate directly in applying and creating interactive media. The stages in this activity are material delivery, training and mentoring. The results of the activity show that teachers have been able to use Quizizz in making simple interactive media. This is indicated by the training participants already having accounts and material topics created in each Quizizz account. In addition, the participants also knew how to conduct learning evaluation activities through giving interactive quizzes to students using QR. Based on the aspects of knowledge and skills of trainees related to the use of Quizizz before the training activities were carried out, the average was 47.67% only. Then after the training activities took place and were re-evaluated through the administration of the posttest, an increase in the aspects of knowledge and skills in using Quizizz was an average of 77.76%. Participants have been able to create interactive learning media based on Quizizz. In addition, this activity is very helpful for teachers in supporting their competence.